Slowing growth: More than a rough patch - M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
Across the world, a structural growth slowdown is underway: at current trends, the global potential growth rate - the maximum rate at which an economy can grow without igniting inflation - is expected to fall to a three-decade low over the remainder of the 2020s. The slowdown could be even more pronounced if financial crises erupt in major economies and spread to other countries, as these types of episodes often lead to lasting damage to potential growth. A persistent and broad-based decline in long-term growth prospects imperils the ability of emerging market and developing economies (EMDEs) to combat poverty, tackle climate change, and meet other key development objectives. These challenges call for an ambitious policy response at the national and global levels.
Keywords: E30; E22; E32; E37; F14; O20; O47; 330; production function; investment; trade; emerging and developing economies